Turkey's development strategy in the light of the economic development of Europe - Werner Gumpel (Intereconomics, 1980)
The Turkish Government intends to apply for EC membership later this year. The prospect of accession was opened to Turkey already by the EC association agreement of 1963. The world-political events pivoting on Afghanistan have greatly improved the chances for Turkey's admission to the EC—despite all the economic problems which Turkish membership involves for the EC and for Turkey itself. Prof. Gumpel analyses these problems here.
Keywords: 330; Development Strategy